Copper market in view of sustainable global trends: demand forecast and systematic review of secondary sources - Soares, Aline Fernanda (2023)
Governments around the world have pursued alternatives to fight climate change in face of growing evidence of environmental risks. The transition to a low carbon energy matrix has received special attention, particularly with incentives to solar and wind energy and electric vehicles. These trends are intertwined with electricity, and the use of copper stands out following its property of high electrical conductivity. As emerging technologies, however, there are uncertainties regarding their evolution and how this will impact copper demand. On the other hand, copper supply is not as price elastic as other commodities, given that the time to discover a mineral deposit and develop a mining project is long. In this context, this study aimed to assess the possible paths of copper-intensive modern technologies, namely solar and wind energy and electric vehicles, and forecast global copper demand. Additionally, this study sought to understand the market dynamics of secondary sources of copper, which could be an option to the extraction of virgin ores. Growth in solar and wind energy technologies and electric vehicles has been consistent and robust, with solar and wind installed capacity rising annually 33.2% and 13.9%, respectively, from 2010 to 2021 and electric vehicles fleet increasing annually 86.6% in the same period, according to the International Energy Agency. However, comparing different scenarios for these trends from the same agency and adding the uncertainty regarding the copper content in these technologies, copper demand from solar and wind energy and electric vehicles can differ by approximately 3.5 million tonnes by 2030. Three autoregressive distributed lag models were tested to forecast copper demand and assess the impact of solar and wind energy and electric vehicles on the estimations. This analysis pointed to a difference of 5 million tonnes in copper consumption forecast for 2030 between the model with and without taking into account electric vehicles and renewable energies in the optimistic scenario. Conventional econometric models that include only explanatory variables related to economic activity and prices can underestimate the potential growth of copper demand, although the used methodology can overestimate the potential growth, given the short period of data for solar and wind energy and electric vehicles. Based on a selection of 42 articles from two databases, this study identified that the availability of secondary sources of copper depends on the in-use stock of copper, breakdown of the end-use sectors, product lifetime, scrap collection rate, recycling efficiency, copper prices, and trade barriers. They should be taken into consideration in an integrated way for the purpose of policy development, having in mind that good environmental and social recycling practices should be followed globally so that recycling has indeed an advantage over virgin materials and the energy transition is underpinned by low-carbon processes throughout the supply chain.